Christmas Tree Bush Fences, Hammock Lake Wetland Protection - Anderson, Sean (California State University Channel Islands Library)
By October 1995, the brush fence had trapped enough sediment for marsh plants to grow behind and inside the fence. As the brush fence continues to trap sediment, the marsh will expand and serve as a barrier to the waves from the bay and as new habitat for fish and wildlife.